Ground Water-Quality of Coastal Kanyakumari District, South India - Sakthykumari, I.; Vijayan, Aathira; Umayoru Bhagan, V.; Anbu, M. (Asian Journal of Chemistry, 2016)
Groundwater quality in coastal region became a matter of concern due to continuously changing environment and increasing industrial and social activities that influence the water quality directly or indirectly. This survey is an attempt to assess the ground water quality along the western coast of the Kanyakumari district, Tamil Nadu, South India. Groundwater samples from sixteen representative open and bore wells from six coastal villages along the coast were collected and preserved separately as per the standard methods. Parameters such as temperature, pH, conductivity and salinity were measured at the site. Quality of groundwater at many of the stations showed near normalcy and physico-chemically safe for drinking purpose. The central region of the station Manakkudy showed normalcy, whereas the results obtained from south (S2) and north (S3) regions of Manakkudy showed higher levels of sulphate 278 mg/L (S2), 242.8 mg/L (S3) and chloride 1810 mg/L (S2), 2710 mg/L (S3). This may be due to the seawater intrusion and mixing of leachate from the coir retting zones. Also magnesium levels in these stations are beyond the permissive limit, which again confirms the contamination and unsuitability for drinking purpose.